A new species of Aethiopella Handschin, 1942 (Collembola, Poduromorpha, Neanuridae) from Neotropical Region, with comments on the genus - Paz, Raiane Vital Da; Queiroz, Gabriel Costa; Bellini, Bruno Cavalcante (Zootaxa, 2019)
Aethiopella Handschin, 1942 as other Pseudachorutinae (Neanuridae) presents a diagnosis with overlapping characters when compared to other similar genera, especially Halachorutes Arlé, 1966, Ceratrimeria Börner, 1906 and Pseudachorutes Tullberg, 1871. This condition, combined to several gaps on the knowledge of described species and a wide range of morphological differences within the genus, reinforces the need of its revision, since it can be an artificial group. In spite of that, a new species, Aethiopella ricardoi sp. nov., is described and illustrated. It resembles the other five Neotropical taxa of Aethiopella but is unique by the combination of fourth antennal segment with trilobed apical bulb and 7 dorsal sensilla, lack of dorsolateral S-microchaeta (ms); postantennal organ with 13–19 vesicles; mandibles with 7–8 teeth; maxillae apically hooked; and tibiotarsi I–III with 19/19/18 chaetae, respectively, with M chaeta slightly basally displaced. We also present an updated diagnosis of Aethiopella based on current knowledge of Pseudachorutinae, a table comparing all species, a key to Neotropical taxa and remarks on the genus.